Dural Arteriovenous Fistulas - Regarding Two Clinical Cases - Fernandes, Cristiana; Varanda, Sara; Amorim, José Manuel; Alves, José Nuno; Ferreira, Carla (International Journal of Innovative Research in Medical Science, 2021)
Dural arteriovenous fistulas (AVF) are rare intracranial vascular malformations, consisting of communications between dural venous arteries and sinuses, meningeal veins, cortical veins, or combinations thereof. In most cases the etiology is unknown. The clinical presentation is determined by the location and mainly by the drainage pattern. The recognition of this rare clinical entity is essential for an early diagnosis and intervention, to avoid the potentially serious complications of the disease, such as, intracranial hypertension, vascular dementia, hemorrhage, among others.